Interdisciplinary learning and teaching in higher education [ theory and practice - Chandramohan, Balasubramanyam , 1955-; Fallows, Stephen J. (Routledge, 2009)
Grounded in research and exploring the issues and tensions provoked by interdisciplinary learning, this is the first book to provide practical advice and guidance from around the world to improve the quality of teaching and learning within this area